Epoxide-functionalization of polyethyleneimine for synthesis of stable carbon dioxide adsorbent in temperature swing adsorption - Choi, Woosung (Nat Commun, 2016)
Amine-containing adsorbents have been extensively investigated for post-combustion carbon dioxide capture due to their ability to chemisorb low-concentration carbon dioxide from a wet flue gas. However, earlier studies have focused primarily on the carbon dioxide uptake of adsorbents, and have not demonstrated effective adsorbent regeneration and long-term stability under such conditions. Here, we report the versatile and scalable synthesis of a functionalized-polyethyleneimine (PEI)/silica adsorbent which simultaneously exhibits a large working capacity (2.2 mmol g(−1)) and long-term stability in a practical temperature swing adsorption process (regeneration under 100% carbon dioxide at 120 °C), enabling the separation of concentrated carbon dioxide. We demonstrate that the functionalization of PEI with 1,2-epoxybutane reduces the heat of adsorption and facilitates carbon dioxide desorption (>99%) during regeneration compared with unmodified PEI (76%). Moreover, the functionalization significantly improves long-term adsorbent stability over repeated temperature swing adsorption cycles due to the suppression of urea formation and oxidative amine degradation.